Teaching factory 2.0: The new approach to teaching factory concept - Boejang, Hambali; Sundi @ Suandi, Syahrul Azwan; Abdul Rasib, Amir Hamzah; Ahmad, Umi Hayati; Paijan, Lailatul Harina; Hassan, Muhammad Zahir (2024)
This study presents the new approach to the teaching factory concept that the Teaching Factory of Universiti Teknikal Malaysia Melaka has adopted. Teaching Factory (TF) provides technical knowledge and skills from industry to manufacturing engineering students. However, in Malaysia, the active involvement of industries in education is insufficient. Moreover, the practical project from the industry used in the classroom as the case study is constrained by the duration of each semester. However, a teaching factory with qualified educators offers an opportunity for the TF to play the role of the faculty’s industrial partner. Similarly, a new product development project can be introduced for the students to indulge in real experimental learning for 3 to 4 semesters. The learning process exposed the students to theories and experiences, conducted by qualified educators and industrial partners through seminars and practical sessions. A product development team was formed, and the product development process started with the design brief and ended with a preproduction prototype. The performance of the product development project was based on its effectiveness and efficiency. The effectiveness was measured through customer acceptance, represented by intellectual property registration, and awards received. Meanwhile, the efficiency was represented by the product development lead time required to fabricate the intended functional prototype. The new concept of TF implementation is considered successful and significantly beneficial to the participants or students. The new concept has also developed the ability of the students to work together and generate the 3D CAD data, engineering build-of-material (EBOM), and operation management documents of manufacturing engineering. The new approach to TF is named Teaching Factory 2.0. It is a viable conceptual approach to the existing teaching factory concept since it integrates holistically the main pillars of knowledge: education, research, and innovation.